The Influence Of Process Parameters Of Electrophoretic Deposition (EPD) Of Carbon Nanotubes (CNTs) On Brass Wire For Electrical Discharge Machining (EDM) - Mohd Hishamuddin, Mikail Lim (2017)
Recently, the product came from carbon nanotubes (CNTs) are very impressive due to their mechanical, electrical and thermal properties. This can lead to expend the usage of this carbon nanotube composite in many various ways, including the usage inside the advance manufacturing fields, especially on wire electrical discharge machining (WEDM). In WEDM, wire breaks are the main issue to be tackled. This research aims to study the feasibility of processing parameter that would affect the properties of the coated EDM wire with carbon nanotubes (CNTs) through electrophoretic disposition (EPD) process. This wire cutting tools, specifically brass, are being chosen to be the electrode in this process in order to insulate it with CNTs composite. By using Aqueous Solution (CNT/Ethanol) in room temperature, the experiment is conducted and relaying on the process parameters such as polarity and supply voltage used. With the supply DC voltage of 20V, it is sufficient to create the deposition effect on the brass wire. Duration on 30mins are seems relevant enough to allow the deposition process to occur with 0.5mg/L of CNTs. The usage of 0.3% PVA as a binder is optional. With the same distance along the two electrodes it provides the desire deposition compared to the non-linear distance between it. This EPD suspension with the brass wire as the electrode given the Anodic type of EPD. The formation of cylindrical shape of MWCNT with the SEM image deposition on brass wire with Galvanize Iron as the counter electrode creating continuous twisting and bundles of MWCNT. A highly interconnected thin petal-like crystallites, forming relatively large grains in the shape of globular features with size larger than 1 μm when Graphite is acting as the counter electrode. Deposition of Galvanize Iron otherwise shows the most excellent deposition when SEM image provides a rearrangement of the MWCNT in a crystallinity of the nano-particles structure.